The Social Support Influence on Psychological Well-Being among Converts in Malaysia - Yasin, Nazri (International Journal of Psychosocial Rehabilitation, 2020)
Psychological well-being consists of positive relationships with others, personal mastery, autonomy, a feeling of purpose and meaning in life, and personal growth and development. This study was conducted to identify the effect of social support on psychological well-being among the converts. The study was conducted on 70 converts from Pertubuhan Kebajikan Islamiah Malaysia (PERKIM) and Institut Dakwah Islamiah PERKIM (IDIP), Malaysia. Respondents were selected based on the criteria set out by the study aged 18 years and above and had converted to Islam for at least a year. Inference analysis is used to test the influence between social support variables and psychological well-being. A T-test is also used to test the mean difference for social support variables and psychological well-being. The findings show that there is a significant influence between social support and the well-being of converting psychology. These studies can contribute to the development of the psychology field, especially in the study of converts in the Asian country. This article also has the potential to be a reference to governments and non-governmental organizations in drafting policies or modules, especially for the converts.